2013
DOI: 10.1038/labinvest.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Smad signaling by 3′-deoxyadenosine: a mechanism for its anti-fibrotic potential

Abstract: Cordyceps militaris has been used in Eastern countries for the treatment of various diseases including chronic kidney diseases. However, there are no reports that identified its active entities and molecular mechanisms underlying its therapeutic effectiveness. 3 0 -Deoxyadenosine is a major nucleoside derivative isolated from C. militaris. Some reports suggested that both C. militaris and 3 0 -deoxyadenosine have anti-inflammatory and anti-fibrotic effects. In the present report, we investigated whether and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The other functional component, cordycepin, can reduce TGF-β1, Smad2/3, α-SMA, and COL1A1 protein levels. Previous study reported that cordycepin can interfere with the TGF-β1 signaling pathway by inhibiting Smad protein levels and phosphorylation, thereby preventing the activation of HSCs [13]. Although DOW cannot reduce TAA-induced TGF-β1, Smad2/3, and p-Smad2/3 protein levels, it can considerably reduce α-SMA and COL1A1 protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other functional component, cordycepin, can reduce TGF-β1, Smad2/3, α-SMA, and COL1A1 protein levels. Previous study reported that cordycepin can interfere with the TGF-β1 signaling pathway by inhibiting Smad protein levels and phosphorylation, thereby preventing the activation of HSCs [13]. Although DOW cannot reduce TAA-induced TGF-β1, Smad2/3, and p-Smad2/3 protein levels, it can considerably reduce α-SMA and COL1A1 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CM-fermented cordycepin has antioxidative and anti-inflammatory effects [11,12]. Cordycepin, a CM metabolite, can inhibit Smad phosphorylation and phosphate levels, thereby interfering with TGF-β1 signaling and inhibiting the activation of HSCs [13]. The described studies have indicated that using DOW as the culturing water can help increase the active components of CM and its liver protection functions.…”
Section: Introductionmentioning
confidence: 99%
“…101 Cordycepin (3 0 -deoxyadenosine) interferes with the TGF-b1 and bone morphogenetic protein signaling through downregulation of Smads, which might be the underlying anti-fibrotic effect of this agent. 102 Moreover, cordycepin markedly blocks TGFb1-mediated activation of renal interstitial fibroblast cells through up regulating anti-fibrotic hepatocyte growth factor (HGF) at both the gene and protein levels. 103 In addition, one study proved that bailing capsule can reduce the expression of TGF-b1 and CTGF in rats with DKD, which can reduce renal tissue injury.…”
mentioning
confidence: 99%
“…The inhibition of MMP is a promising strategy in skin cancer and photoaging therapy [95]. Moreover, COR represses lung fibrosis by increasing E-cadherin expression and decreasing vimentin levels [96] and inhibits kidney fibrosis by inactivating targets (CAGA box, BRE and Smad1/2/3) and stimulating eIF2α [97]. In addition, COR plays a significant role in suppressing atopic dermatitis [69].…”
Section: Other Medicinal Values and Biological Applicationsmentioning
confidence: 99%